Innovation for sustainability : small farmers facing new challenges in the evolving food systems - Brunori, Gianluca; Grando, Stefano (Bingley, U.K. : Emerald Publishing Limited, 2020)
Small farms represent important components of food systems and rural areas, as sources of occupation and livelihood, factors of socio-economic diversity, cradles of grass-roots innovation and experimentation. Their capacity to adapt and to contribute positively to societal challenges depends on the strategies they can develop and their ability to innovate. The book provides an in-depth exploration of the determinants, dynamics and outcomes of rural and agricultural change processes, with a special focus on the role of small and family farming. Covering both the system and the farm level of analysis, the authors offer a comprehensive view of approaches and models capable to grasp different complementary aspects of the development trajectories followed by farms, food systems and territories facing multi-dimensional drivers of change and exposed to a range of vulnerability factors. The emerging characters and roles of innovation networks and social learning, as well as the decision-making processes at the farm level are explored in particular depth, with attention to the multi-dimensional societal expectations vis-à-vis agriculture, small farms and rural areas, with specific attention to food and nutrition security concerns.
Chapter 1. Small farming and the food system / Stefano Grando, Gianluca Brunori, Teresa Pinto-Correia, Lee-Ann Sutherland -- Chapter 2. Small farming and food and nutrition security / Gianluca Brunori, Tessa Avermaete, Fabio Bartolini, Natalia Brzezina, Stefano Grando, Terry Marsden, Erik Mathijs, Ana Moragues-Faus, Roberta Sonnino -- Chapter 3. Unpacking food systems / Gianluca Brunori, Tessa Avermaete, Fabio Bartolini, Natalia Brzezina, Terry Marsden, Erik Mathijs, Ana Moragues-Faus, Roberta Sonnino -- Chapter 4. The vulnerability of food systems / Gianluca Brunori, Tessa Avermaete, Fabio Bartolini, Natalia Brzezina, Terry Marsden, Erik Mathijs, Ana Moragues-Faus, Roberta Sonnino -- Chapter 5. Food systems as assemblages / Gianluca Brunori,Francesca Galli, Stefano Grando -- Chapter 6. Small farms' behavior: Conditions, strategies,performances / Stefano Grando, Fabio Bartolini, Isabelle Bonjean, Gianluca Brunori, Erik Mathijs, Paolo Prosperi, Daniele Vergamini -- Chapter 7. Small farms and innovation / Gianluca Brunori, Jet Proost, Sigrid Rand -- Chapter 8. Innovation policies for sustainable, resilient, food secure systems / Gianluca Brunori, Jet Proost, Sigrid Rand.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Family farms -- Technological innovations; Food supply; Food security; Technology & Engineering -- Agriculture -- General; Sustainable agriculture